Shariah Review: On Waqf Property Act 2020 - Hafiz Hassan Madani (jihat-ul-islam, 2022)
In September 2020, legislation was enacted in national and provincial assemblies for Islamabad and all provinces under the title of ’Waqf Property Act 2020’ and similar names, in which the previous laws were amended along with some new laws. Formal notices have also been served to custodians of dedicated properties in Punjab and Sindh provinces and advertised in the national media to fulfill the requirements of newly enacted ’’Waqf Property Act 2020’’. According to the Pakistani Constitution, no law shall be made against Islam, the following is a sharia analysis of the new act in view of the original passages and authentic references of it. In which the mandatory government’s permission is criticized for preaching of Islam, as well as transferring ownership of dedicated property to the government and ignoring the special Shariah rulings on waqf.